Hydrochemistry and surface water - groundwater interactions in an anthropically disturbed mountain river (Sierras Pampeanas, central Argentina) - Campodonico, Verena Agustina (2024)
The surface water - groundwater interactions in a small anthropically affected mountain watershed (Salsipuedes River) in Sierras Pampeanas (central Argentina) was analyzed and quantified by means of 222Rn mass balance modeling, and its implications in hydrochemistry and water quality was examined. Surface waters, springs and groundwater were sampled during the 2021-2022 hydrological year, and the major dissolved composition was determined. The studied waters are alkaline, showing an evolution from medium mineralized (1.5 < ∑+ < 3 meq L-1) to mineralized type (3 < ∑+ < 6 meq L-1) downstream. In general, waters are of the bicarbonate – calcium type with no spatial or seasonal variations. This composition is mainly controlled by silicates weathering. 222Rn modeling indicates that near the headwaters the Salsipuedes River recharges the aquifer, losing 1.2% and 2.4% of its discharge during the dry and wet seasons, respectively. Downstream, the system changes its hydrological behavior and the river acts as a gaining stream; i.e, it receives groundwater inflow. The magnitude of this inflow varies seasonally, being greater in the wet season (1.5 - 2.2% of total flow) than in the dry season (less than 0.25%) due to a rise in the water table level as a result of direct recharge of the phreatic aquifer. Anthropic influence is noticeable in nitrate and chloride concentrations, which are derived from domestic wastes and septic wells. The highest concentrations of these ions in surface waters are found in the urbanized area, where the river stretch corresponds to a gaining stream, reflecting that even small amounts of groundwater inputs can alter the chemical composition of streams. A temporal analysis also showed a variable response of the system to the increasing anthropic pressure and climatic events such as ENOS, which affect not only water availability but also its quality, highlighting the vulnerability of small mountain watersheds.